The Population of the Ros’ River Basin during the Pre-Mongol and Golden Horde Periods - Bubenok O.B.; Golovko A.B. (Золотоордынское обозрение, 2021)
Research objectives: To determine both the ethnic structure of the population of the Ros’ river basin before the arrival of the Mongol armies in the first half of the thirteenth century and the changes to the local population after the inclusion of this region into the Golden Horde. Materials: Written sources of Old Russian, Byzantine, Western European, Persian, and Mongolian origin; results of archaeological excavations in the Ros’ river basin; toponymy data. Results and novelty of the research: For the first time ever, a comparative analysis of the evidence of written sources and archaeology about the ethnic structure of the population of Ros’ river basin was carried out not only for the pre-Mongol time, but for the Golden Horde period as well. As a result, it has been made possible to trace the stages of change among the former population of region. It has been established that for the beginning of the thirteenth century, the left bank of the Ros’ river was dominated by a Turkophone population known in written sources as the Torks or Black Hoods. The arrival of the Mongols here led to the migration of significant groups of this population to the steppes of Eastern Europe. However, some Torks continued to live in their former locations according to the data of toponyms and hydronyms. At the same time, the Golden Horde rulers began to populate the banks of the Ros’ river by the militarized immigrants from the Circassian lands and other regions of the Golden Horde. This has been proven by the results of excavations of barrows near the Yablonovka and Tagancha villages. This resettlement was the result of a pragmatic policy of the Golden Horde rulers aimed at strengthening this part of the border between the Ulus of Jochi and Rus’, running along the Ros’ rive.